Identifikasi Senyawa Fraksi Larut n-Heksana Rimpang Temu Mangga (Curcuma mangga Val) Menggunakan LC-MS/MS dan Review Potensinya sebagai Antibakteri: Identification of Compounds Soluble n-Hexane Fraction of Rhizome of Temu Mangga (Curcuma mango Val) Using LC-MS/MS and Review of its Potential as Antibacterial - Purwantinigsih Sugita; Risda Fardilya Nihayah; Moch Ikkbal Aditya Kasmaran; Gustini Syahbirin; Auliya Ilmiawati; Budi Arifin; Luthfan Irfana (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Plants are like the pharmaceutical industry that provides products that have the potential as active medicinal ingredients. In order to search for compounds useful for health, the purpose of this study was to identify secondary metabolites of Curcuma mango (temu mango) growing in the experimental garden of Biopharmaca LPPM IPB and review its activity as antibacterial. Identification begins with phytochemical screening, then separation and purification by chromatographic techniques. Intersection mango simplicia was extracted with methanol, and the crude extract of methanol was partitioned with n-hexane, ethyl acetate, and methanol, respectively. The n-hexane soluble fraction was carried out by phytochemical tests, fractionation by vacuum liquid chromatography (KCV) and radial (KR), and the selected fractions was analyzed by LC-MS/MS. The results of the phytochemical test of the soluble n-hexane fraction showed a positive presence of alkaloids and terpenoids through successive tests with Mayer, Wagner, Dragendorff (alkaloid), and Lieberman-Burchard reagents. Fractionation of the n-hexane soluble fraction with KCV resulted in 9 fractions (H1-H9) and the H5 fraction showed good separation between spots in the n-hexane: ethyl acetate eluent mixture (97:3). Purification of H5 with KR obtained 7 fractions (H5.1-H5.7). Based on LC-MS/MS, the H5.2 fraction was dominated by the terpenoid group, and the results of the literature review showed the contribution of terpenoids as antibacterial compounds